PERANCANGAN POMPA SENTRIFUGAL UNTUK SISTEM SALURAN AIR LAUT PADA AREAL PENGGARAMAN - Ilham Hasbiullah (Politeknik Aceh, 2016)
KembangTanjung is a village located on the coast of Aceh Pidie district. Most of the community's economy to develop business in marine. Conditions of the process of making salt salt farmers do almost all of Indonesia are still using traditional technology. Development of this technology is absolutely necessary in all aspects of salt production carried salt farmers in Indonesia. Nevertheless, this development must go through stages which certainly is influenced by the value of investing in these technologies. The technology used in KembangTanjung salt farmer is a legacy technology of the salt farmers who are the ancestors of the farmers. Cultural affinity salting used will lead to reluctance to accept the new technology. To solve the problem, it is necessary to design a centrifugal pump which can reduce the work of farmers. Centrifugal pumps are designed is to use materials that can be used as a seawater pump. The sea water will cause a degree of corrosiveness of the metal material so high that fiberglass on volute and impeller components will have better optimization. The pump will be placed on the shore rather high to avoid the rising tide of sea water and then pump the sea water will flow into the storage tank through a pipeline that will be built in accordance with the needs in the area of sea water salinity. The pump is designed to have eisiensi 80% in 2000. The specific speed pump impeller diameter is 20 cm. on the condition of the water flow rate of 100 m3 /s on rotated at 500 rpm, the pump is moving at the wind of 2.5 m / s.